See me play - Meisel, Paul (Holiday House, 2019)
In this easy-to-read book, a playful pack of dogs chase a ball that is caught by a bird, a whale, and a lion.
Guided reading level C.
Keywords: Play -- Juvenile fiction; Dogs -- Juvenile fiction; Animals -- Juvenile fiction; Play -- Fiction; Dogs -- Fiction; Animals -- Fiction; Readers (Publications)